The Optimization of Platelet Aggregates in Orbital Disorders. An Integrative Review - Brunetto, J. [UNESP]; Pesqueira, A. [UNESP]; dos Santos, D. [UNESP]; Goiato, M. [UNESP] (Professionals Publications, 2023)
Due to physical, chemical, and/or pathogenic trauma, the loss of vision, and sometimes of the eyeball, causes to these patients the need of ocular prostheses. For its regeneration and decontamination different approaches have been investigated, but many have a long-term side effect. An interesting alternative is the adhibition of platelet aggregates, obtained from the donor patient’s own blood. Purpose. To compare studies and unite the best treatment techniques that use blood- derived concentrates in the ophthalmic cavity. Methods. After analyzing the eligibility criteria, of 1.495 initial articles, 23 studies were selected for the integrative review, published in English and between 2011 and 2021. Although the use in eye drops is the most used, the applications of this content have been successfully extended to other necrosis disorders, after LASIK surgery, after ocular burns and even in patients with severe tear dysfunction secondary to Sjogren’s Syndrome, Stevens-Johnson Syndrome and pemphigoid. Despite the apparent advantages of re- epithelialization and reduction of inflammation, most techniques are often inadequately regrouped since their inception. Due to the large number of techniques, classifying, comparing and interpreting the preparation and terminology of blood products, has highlighted the difficulty of its systematization. Thus, it is concluded that platelet aggregates present promising results in patients with ophthalmic disorders. Further clinical studies are recommended for a standardization of the technique and investigation in anophthalmic patients.
Keywords: blood products; ocular; platelet aggregates; platelet concentratesm; platelet rich plasma